Policing and the youth question : civil society and the state in the urban periphery in Ireland - Bowden, Matthew (Trinity College (Dublin, Ireland). Department of Sociology, 2008)
This thesis is an exploration of the relations between state and civil society actors involved in the local governance of youth crime and disorder in urban peripheral settings in Ireland. The dissertation aims to develop a distinct theoretical framework and methodology for the analysis of youth crime and disorder prevention.
Keywords: Sociology, Ph.D.; Ph.D. Trinity College Dublin